Internalising health-economic impacts of air pollution into climate policy: a global modelling study. Issue 1 (January 2022) - Reis, Lara Aleluia; Drouet, Laurent; Tavoni, Massimo
Summary: Background: Climate change and air pollution are two major societal problems. Their complex interplay calls for an advanced evaluation framework that can support decision making. Previous assessments have looked at the co-benefits of climate policies for air pollution, but few have optimised air pollution benefits. In our study, we lay out a modelling framework that internalises air pollution's economic impacts on human mortality, while considering climate constraints and aerosol feedback. Methods: We developed a modelling framework based on an integrated assessment model (World Induced Technical Change Hybrid [WITCH]) designed to assess optimal climate change mitigation policies. We included structural and end-of-pipe measures in a detailed process integrated assessment model, that is hard-linked to air pollution and climate models. We analysed a large set of baseline scenarios, including five shared socioeconomic pathways (SSPs). SSP scenarios were also tested with three different levels of value per statistical life, and were combined with the Paris Agreement temperature targets (TTs), focusing on the 2°C and 1·5°C TTs by the end of the century. Findings: We found that, in the baseline scenarios, where no policies are applied, the number of annual premature deaths grew before declining slightly to 4·45 (range 3·86–6·11) million annual premature deaths by 2050. Reaching the Paris Agreement TT decreases mortality by approximately 0·47 million premature deaths by 2050 (up to 1·28 million premature deaths in SSP3 –1·5°C) with respect to the baseline. We showed that welfare-maximising policies accounting for air pollution benefits reduces premature mortality by 1·62 million deaths annually. This is three times greater than the co-benefits of climate policies. China is the region where most of the avoided mortality is possible, whereas the reforming economies (ie, non-EU eastern European countries, including Russia) region has the greatest welfare benefits. We find that global and regional welfare increases when air pollution impacts are internalised, with no negative repercussions on global inequality. Interpretation: Air pollution control strategies are found to be an important complement to structural emission reductions. Accounting for air pollution impacts reduces climate mitigation costs and inequality and increases global and regional welfare. Results are robust to a broad set of scenarios and assumptions, including debated normative choices on how to value improved health. Funding: EU Commission projects: INNOPATHS, NAVIGATE, ENGAGE, and COMMIT.